Developments in in-situ (trans) esterification for biodiesel production: A critical review. (July 2016) - Go, Alchris Woo; Sutanto, Sylviana; Ong, Lu Ki; Tran-Nguyen, Phuong Lan; Ismadji, Suryadi; Ju, Yi-Hsu
Abstract: Biodiesel is a biofuel used as an alternative for petroleum diesel. The main obstacle in the widespread use of biodiesel lies mainly on its cost and current state of the technology to process a wide array of feedstock. The cost of biodiesel production is still high compared to that of petroleum based diesel fuel. The decrease of production cost can be achieved through the utilization of cheap, low quality feedstock and the development of simpler production process. In - situ (trans) esterification (ISTE) is an alternative route in synthesizing or producing biodiesel. ISTE involves lesser steps as it eliminates the need for lipid or oil extraction prior to (trans) esterification. A detailed comparison of the various strategies, mechanism involved and technologies developed since 1985 on ISTE processes is described in this review. This review tackles several technological gaps needing to be bridged and addressed in future studies. Furthermore, future prospects and possible developments in ISTE is also looked into.